Product development and characterization of a lipid-based Ayurvedic polyherbal formulation: Kalyanaka Ghrita - Yashika Singh; Amzad Ali Ansari; Rajendra Prasad Sharma; Saroj Moreshwar Parhate; Thakur Rakesh Singh (Journal of Ayurveda and Integrative Medicine)
Background: Kalyanaka Ghrita (KG) is polyherbal oleaginous medicament consisting of extracts from twenty-eight different plants, indicated for management of psychosomatic disorders like Unmada (Schizophrenia), Apasmara (Epilepsy) and numerous other ailments. Objective: To develop and validate standard manufacturing procedure of KG by following Ayurvedic principles in three batches to ensure process uniformity and standards. Materials and methods: Three batches of KG were prepared by adopting principles of Ashtanga Hrudya and Ayurvedic Formulary of India to ensure consistency in manufacturing process. Observations during process such as temperature, duration were recorded. KG was subjected to chief desired characteristics, organoleptic (color, odour, taste, texture, touch), physicochemical (acid value, peroxide value, iodine value, saponification value, loss on drying, refractive index, specific gravity, mineral oil, rancidity test, viscosity) as per pharmacopeial standard. Chromatographic screening and fingerprinting of KG were conducted through GCMS whereas quantification of curcumin and chebulagic acid biomarkers were assessed through HPLC. Results: Average yield of KG was 83.41%, with average intermittent heating duration of 20.35 h subsequently divided into three days. Temperature throughout preparation ranged from 66 °C to 101 °C. KG was pale olive in colour, exhibiting pleasant taste, characteristic smell, and soft texture. Organoleptic and physicochemical characters were comparable for three batches of KG while safety parameters were found within permissible limits. Conclusion: Pharmaceutical standardization of Kalyanaka Ghrita is necessary for establishing biological and chemical profile of formulations. Present study recommends use of coarse powdered ingredients for optimal yield during pharmaceutical process, and heating up to Madhyama Paka stage calibrated over three days with average temperature of 85 °C. The data obtained from this study may contribute to future research and development activities, serving as a basis for manufacturing standards of KG.